Analisis Strategi Orientasi Pasar Dan Penggunaan Sosial Media Instagram Terhadap Keunggulan Bersaing - Resti Juwita; Erry Sunarya; Dicky Jhoansyah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine the effect of market orientation and social media on competitive advantage. The method used in this research is descriptive, associative method with a quantitative approach. The sampling technique used in this study was Non Probability Sampling (purposive sampling) and saturated sampling (Census). The samples taken in this study were 36 MSME Food and Beverage companies in Sukabumi City. The data analysis technique used in this research is multiple correlation coefficient, determination coefficient test, simultaneous test (f test), multiple linear regression, and partial test (t test) to determine the extent of the influence of the two independent variables under study on the variable. dependent. The results showed that there was a positive and significant influence of the market orientation variable on competitive advantage of 0.907, and there was a positive and significant influence of the social media variable on the competitive advantage variable of 0.944. As well as the positive and significant influence of market orientation and social media in increasing competitive advantage by 0.930 or 90.3%, while the remaining 0.970 or 9.7% is influenced by various factors outside of this study. From these results it can be seen that market orientation variables and social media have a positive and significant effect in increasing competitive advantage, although the most dominant influence on competitive advantage is market orientation. Keywords: Market Orientation, Social Media, Competitive Advantage